Gangguan fungsi hormon tiroid pada anak penderita infeksi susunan saraf pusat - Rahmad Sumiko; Melda Deliana; Hakimi dr; Siska Mayasari Lubis; Karina Sugih Arto (Majalah Kedokteran Nusantara The Journal Of Medical School, 2014)
Dysfunction of thyroid hormone can occur in children with central nervous system (CNS) infections characterized by decreasing levels of triiodothyronine (T3). Severe CNS infections have symptoms such as seizures, respiratory failure, impaired consciousness, fever, and typical abnormalities on Elektroencephalografi (EEG). Central nervous system infected children with low T3 have tendency of lower survival rate compare to CNS infected children with low thyroxine (T4). Examination of thyroid hormone performed by using vena puncture and lumbar puncture. It was performed before treatment is given. Until now, there are onlyfew case reports of thyroid hormone dysfunction in children with central nervous system infections.Keywords : CNS infection, children, thyroid dysfunction